PELAKSANAAN AUDIT OPERASIONAL UNTUK MENILAI KINERJA KARYAWAN BAGIAN PERSONALIA - Sari, Novi Mustika; Ngumar, Sutjipto (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
In a company, the personnel departmenthas an identic correlation to the human resources in order to achieve the objectives and success of the company. The activity of the personnel department is meant to manage the human resources which include recruitment, selection, position, appreciation, training, and termination ofthe employment relationship. The operational audit in assessing the performance of the employeesin the personnel department can give appropriate recomendation to increase the work quality in the future. The purposes of this research i.e.: (1) to understand the implementation of operational audit in assessing the effectivenes of the performance of the employees in personnel department and (2) to find out and to analyze some factors which have caused the effectiveness and the efficiency of the performance of the employees. The data analysis technique has been done by using descriptive analysis and qualitative analysis approachby collecting the related data with the operational audit in personnel department at PT Multinas Indonesia. The result of this research shows that there are problems in the personnel department at PT Multinas Indonesia i.e. there areworkers who are oftenenteringor quitting, in the final test not only the personnel department which has theauthority to pass the personnel but the division manageral so has the authority and there is no particular employee to run the ability test. But, in general,the activity in the personnel department of PT Multinas Indonesia has been running effectively, efficiently and has met the standards that has been determined by the companyi.e. Company StandardOperational.Keywords:Operational Audit, Personnel, Effectiveness and Efficient.